Practicing the Common Good: The Pedagogical Implications of Catholic Social Teaching - Whitmore, Todd (Teaching theology and religion, 2000)
A persistent question for pedagogy is that of whether and how the content of a course ought to shape the teaching method. Both the understanding of practical reason and the substantive concepts of modern Catholic social teaching support a classroom dynamic of a relatively egalitarian dialectic. The author grounds the case for this pedagogy in the understanding of practical reason as found in Aristotle and Thomas Aquinas, and shows that such an understanding is continued in modern Catholic social teaching. He then shows how the social teaching's substantive move to a more egalitarian social theory reinforces the egalitarian mode of reasoning. The author and others are attempting to practice this pedagogy in the context of the University of Notre Dame's new Program in Catholic Social Tradition. The investigation as a whole raises the question of whether colleges and universities that have actively maintained religious affiliations have a decided advantage in sustaining an academic culture where faculty and students can practice practical reason.